An Fgr kinase inhibitor attenuates sepsis-associated encephalopathy by ameliorating mitochondrial dysfunction, oxidative stress, and neuroinflammation via the SIRT1/PGC-1α signaling pathway - Yuqiang Liu; Han Yang; Nanbo Luo; Yifei Fu; Fang Qiu; Zhenglong Pan; Xiongjuan Li; Wenling Jian; Xinping Yang; Qingsheng Xue; Yan Luo; Buwei Yu; et al. (Journal of Translational Medicine, 2023)
Abstract Background Sepsis-associated encephalopathy (SAE) is characterized by diffuse brain dysfunction, long-term cognitive impairment, and increased morbidity and mortality. The current treatment for SAE is mainly symptomatic; the lack of specific treatment options and a poor understanding of the underlying mechanism of disease are responsible for poor patient outcomes. Fgr is a member of the Src family of tyrosine kinases and is involved in the innate immune response, hematologic cancer, diet-induced obesity, and hemorrhage-induced thalamic pain. This study investigated the protection provided by an Fgr kinase inhibitor in SAE and the underlying mechanism(s) of action. Methods A cecal ligation and puncture (CLP)-induced mouse sepsis model was established. Mice were treated with or without an Fgr inhibitor and a PGC-1α inhibitor/activator. An open field test, a novel object recognition test, and an elevated plus maze were used to assess neurobehavioral changes in the mice. Western blotting and immunofluorescence were used to measure protein expression, and mRNA levels were measured using quantitative PCR (qPCR). An enzyme-linked immunosorbent assay was performed to quantify inflammatory cytokines. Mitochondrial membrane potential and morphology were measured by JC-1, electron microscopy, and the MitoTracker Deep Red probe. Oxidative stress and mitochondrial dysfunction were analyzed. In addition, the regulatory effect of Fgr on sirtuin 1 (SIRT1) was assessed. Results CLP-induced sepsis increased the expression of Fgr in the hippocampal neurons. Pharmacological inhibition of Fgr attenuated CLP-induced neuroinflammation, the survival rate, cognitive and emotional dysfunction, oxidative stress, and mitochondrial dysfunction. Moreover, Fgr interacted with SIRT1 and reduced its activity and expression. In addition, activation of SIRT1/PGC-1α promoted the protective effects of the Fgr inhibitor on CLP-induced brain dysfunction, while inactivation of SIRT1/PGC-1α counteracted the benefits of the Fgr inhibitor. Conclusions To our knowledge, this is the first report of Fgr kinase inhibition markedly ameliorating SAE through activation of the SIRT1/PGC-1α pathway, and this may be a promising therapeutic target for SAE. Graphical Abstract